KARDS Model: An Alternative Approach to Language Education - Santiana, Santiana; Enriquez, Alexis; Marzuki, Abdul Gafur; Mahmud, Rashed; Ghofur, Abdul (TLEMC (Teaching and Learning English in Multicultural Contexts), 2024)
Students can be motivated by making them aware of their intrinsic and extrinsic motivation. Guiding the student could include addressing the subject’s goals, the nature of the activities, and the techniques used to complete the tasks, including supporting them in determining the best ways to learn. Providing learning facilities indicates that the instructor should be able to facilitate and simplify learning. This is essentially characterized as creating and establishing suitable learning settings and providing learning resources. This piece of paper will emphasise a literature review on the KARDS Model as an alternative conceptualization for language training. The review is based on journal papers, conference proceedings, and book chapters that explore Kumaravadivelu's KARDS Model. The scope of this discussion is limited to the following points: (1) presenting Postmodernism as a relevant theoretical framework in the context of language teacher education and (2) presenting the KARDS model as an alternative conceptual outline that can help language teachers address teaching issues more effectively. This finding demonstrates that teachers must keep their knowledge, which serves as their academic medium of communication, up to date in order to survive in academic contexts. Their enhanced professional and personal knowledge is projected to lead to more positive perceptions. This distinction may be justified by the circulation of knowledge transfer and building, the routine exchange of knowledge, and academicians' access to the most recent results.Keywords: Alternative Approach, KARDS Model, and Language Education